2014
DOI: 10.1073/pnas.1320646111
|View full text |Cite|
|
Sign up to set email alerts
|

Spatially robust estimates of biological nitrogen (N) fixation imply substantial human alteration of the tropical N cycle

Abstract: Significance Biological nitrogen fixation (BNF) is the largest natural source of new nitrogen (N) to terrestrial ecosystems. Tropical forest ecosystems are a putative global hotspot of BNF, but direct, spatially explicit measurements in the biome are virtually nonexistent. Nonetheless, robust estimates of tropical forest BNF are critical for understanding how these important ecosystems may respond to global change and assessing human perturbations to the N cycle. Here, we introduce a spatial sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(200 citation statements)
references
References 59 publications
11
185
2
1
Order By: Relevance
“…Facultative symbioses in the tropics make evolutionary sense inasmuch as soil nitrogen availability is typically greater there than at the poles and nitrogen fixation carries a carbon cost for the plant. In support, concurrent research suggested that rates of nitrogen fixation may be less in N-rich tropical forests than previously thought (10). N 2 FP differ in their distribution in northern and southern hemispheres, albeit that N 2 FP are common in the tropics in both hemispheres.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Facultative symbioses in the tropics make evolutionary sense inasmuch as soil nitrogen availability is typically greater there than at the poles and nitrogen fixation carries a carbon cost for the plant. In support, concurrent research suggested that rates of nitrogen fixation may be less in N-rich tropical forests than previously thought (10). N 2 FP differ in their distribution in northern and southern hemispheres, albeit that N 2 FP are common in the tropics in both hemispheres.…”
mentioning
confidence: 67%
“…That insurance and other nitrogen-related advantages have facilitated the spread of N 2 FP throughout the globe and their contributions to global N cycles (37,38). The facultative nature of the symbiosis with respect to soil nitrogen (4,(8)(9)(10)) is augmented by its flexibility in relation to soil water-N 2 FP seldom fix nitrogen under drought conditions (29)(30)(31), although their ability to nodulate may be unimpeded (39) and help restore fixation after drought is relieved. These features facilitate the dominant role played by N 2 FP in both wet and dry tropics as well as large areas of temperate and Mediterranean climates.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem Processes: Nitrogen Cycling N 2 fixation, N mineralization, and (de)nitrification are all regulated by the availability of N. Evidence from wet forests suggests that legumes down-regulate symbiotic N 2 fixation as soil N becomes more available through secondary succession (Batterman et al, 2013;Sullivan et al, 2014a). Similarly, rates of free-living N 2 fixation in soils and the forest floor may decrease with increasing N availability, as seen in wet forests of Puerto Rico (Cusack et al, 2009).…”
Section: Ecosystem Processes: Soil Carbon Dynamicsmentioning
confidence: 99%
“…Because of rapidly increasing rates of N deposition across the tropics (Hietz et al, 2011;Sullivan et al, 2014a), most of the studies included in our review focus on effects of N addition. We develop a conceptual model of how added N affects TDFs; because TDFs may be N-or P-limited, our model considers how responses to N addition may vary between forests with low or high P availability.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the biologic fixation term was not used for P calculation. Since the tea plantation does not use leguminous crop as fertilizers and the biological fixation in tropical forest is known to be less than 10 kg N ha −1 yr −1 (Sullivan et al, 2014), the IN fix is assumed to be between 0 and 10 kg N ha −1 yr −1 . We did not include the loss through denitrification and volatilization within tea field in the calculation of N retention ratio because we did not have good estimates.…”
Section: Element Fluxesmentioning
confidence: 99%